Dermatoglyphic analysis of left-handed individuals in the student population of the Faculty of Mathematics and Natural Sciences Universitas Negeri Padang - Dini Herisanti; Afifatul Achyar; Yuni Ahda (Tropical Genetics, 2023)
Dermatoglyphics is a science that studies fingerprint patterns that can be inherited genetically. Fingerprint patterns can be divided into three patterns, arch, loop, and whorl. Observation of fingerprints is used to determine fingerprint patterns and the relationship between these patterns and the fields of health, education, and criminology. Left-handed is a term for people who predominantly use their left hand as their main hand to carry out daily activities. This research aims to determine the relationship between fingerprint patterns and individuals who tend to carry out activities with the left side of their body (left-handed). The type of research carried out was descriptive research with a cross-sectional sample collection method. The sample was taken from the 2019-2022 student population of the Faculty of Mathematics and Natural Sciences, Padang State University, totaling 100 individuals. The samples were taken in November and December. This research was carried out at the Genetics and Biotechnology Laboratory, Faculty of Mathematics and Natural Sciences, Padang State University. The results of this study show that the dominant fingerprint pattern found in the left-handed individual phenotype is 16 fingerprint patterns, while normal individuals have 5 arch fingerprint patterns. This shows that there is a link between the phenotype of left-handed individuals and dermatoglyphics.